A 3D reconstruction method for pipeline inspection based on multi-vision. (February 2017) - Zhang, Tian; Liu, Jianhua; Liu, Shaoli; Tang, Chengtong; Jin, Peng
Highlights: A new reconstruction method for complex pipeline inspection is presented. A centerline matching and registration algorithm for branched pipeline is proposed. A pose estimation algorithm based on shape aspect graphs for joint is proposed. A pipeline multi-camera measurement system is established to achieve our method. The method's efficiency and accuracy is higher than the present methods. Abstract: A fast and precise 3D reconstruction method for complex pipeline inspection is presented. The reconstruction process is divided into three phases based on multi-vision. A centerline matching and registration algorithm is proposed to achieve the branched and bended pipes' reconstruction. The projected centerline of each pipe is split into several NURBS curves, and these curves are taken as the primitives of matching to be reconstructed and registered precisely. A pose estimation algorithm based on shape aspect graphs is proposed to achieve the joint's reconstruction. The CAD model of each joint is used to obtain its shape aspect graphs as the templates which its edges image matches with. A pipeline multi-camera reconstruction system is established, and validation experiments are carried out. The results show that the proposed method completes a pipeline's reconstruction within 5 min. The reconstruction errors of its pipes and joints are 0.24 mm and 0.496 mm respectively.